Poverty and Vulnerability in Rural South-West Nigeria (2012)
The near failure of various programmes and strategies by successive governments in Nigeria has been linked to the improper diagnosis of poverty as a static concept. There are growing concerns that poverty is not reducing due to the lack of understanding of its dynamic nature and vulnerability to poverty. This study investigates poverty and vulnerability to poverty in rural South-West Nigeria (SWN). Primary data were collected from 582 rural households in a two-wave panel survey (harvesting and lean periods) employing a multi-stage sampling technique. Data were analyzed using; Foster, Greer and Thorbecke (FGT) poverty measure; 3-Stage Feasible Generalized Least Squares (3FGLS); Tobit and Probit regression methods. Poverty lines of N3313.57 and N4093.21 were estimated for the two periods, respectively. Based on these, the incidence of poverty was 35.0% and 43.6% for the first and second periods. At the standard vulnerability threshold of 0.5, 55.7% of rural households in SWN were vulnerable to poverty. A unit increase in household size and dependency ratio aggravated vulnerability by 0.05 and 1.28, while attainment of secondary and tertiary education reduced vulnerability by 0.14 and 0.23, respectively (P<0.01). Vulnerability also translated into significantly (P<0.01) higher poverty by increasing the ex-post probability of becoming poor by 0.34. However, there were some factors related with vulnerability but not poverty and some related to poverty but not vulnerability. The study therefore suggests that poverty alleviation programs must focus not only on those factors which aggravate poverty but also vulnerability, in order to employ several specialized approaches to tackle these multifarious problems.